The Italian national community in Slovenia during the Covid-19 epidemic - Sorgo, Lara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article presents the views and opinions of the members of the Italian national com-munity regarding the organisation of their institutions and schools and regarding state borders with Italy and Croatia during the Covid-19 epidemic in Slovenia. The main purpose of the study, which took the form of a telephone interview, was to explore the situation of the Italian national community during this period. Given the uncertainty awaiting it in the future, the Italian national community will need to find new ways to get closer to its members.
Keywords: čezmejno sodelovanje; državne meje; italijanska manjšina; narodne manjšine; pandemija covid 19; Skupnost Italijanov; Slovenija; šole z italijanskim učnim jezikom